Answer: Peter gets £3
Step-by-step explanation:
Let Angad get x: equation will be 2(3x) + 3x + x = 10
X = 1 = Angad
Peter get 3x = 3*1 = 3
Each letter of the alphabet is worth two times as much as the one before it, implying that the value of each letter rises in mathematical progression. The formula for finding the nth term of an arithmetic progression would be used. I am written as
a + (n - 1)d = Tn
Where
The number of terms in the arithmetic sequence is represented by n.
The common difference of the terms in the arithmetic sequence is represented by d.
The first term of the arithmetic sequence is represented by a.
Tn stands for the nth word.
Based on the facts provided,
n = 26 characters1 Equals a
3 minus 1 equals 2 (difference between 2 letters)
Therefore,
1 + (26 - 1)2 = T26
51 = T26
The formula for calculating the sum of an arithmetic sequence's n terms
is as follows:
[2a + (n - 1)d] Sn = n/2
As a result, S26 is the sum of the first 26 terms.
S26 = 20/2[2 1 + (26 - 1)2] S26 = 20/2
[2 + 50] S26 =
676 = S26 = 13 52
Its 11 cause I’m built different
Answer:
not sure
Step-by-step explanation:
6-4 =2
2*9=18??
I'm not sure, since that was simple math, can you clarify by what you meant the difference of 6 and 4.
Answer:
![\tan \left(\frac{\pi }{2}\right)](https://tex.z-dn.net/?f=%5Ctan%20%5Cleft%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D%5Cright%29)
Step-by-step explanation:
We know that tan(x) is defined as sin(x)/cos(x):
![\tan \left(\frac{\pi }{2}\right),\\\sin \left(\frac{\pi }{2}\right)=1,\\\cos \left(\frac{\pi }{2}\right)=0,\\\\](https://tex.z-dn.net/?f=%5Ctan%20%5Cleft%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D%5Cright%29%2C%5C%5C%5Csin%20%5Cleft%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D%5Cright%29%3D1%2C%5C%5C%5Ccos%20%5Cleft%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D%5Cright%29%3D0%2C%5C%5C%5C%5C)
![\tan \left(\frac{\pi }{2}\right) = 1/0 \\](https://tex.z-dn.net/?f=%5Ctan%20%5Cleft%28%5Cfrac%7B%5Cpi%20%7D%7B2%7D%5Cright%29%20%3D%201%2F0%20%5C%5C)
1/0 is undefined as 0 is in the denominator